Composition and biological activity of essential oil from aboveground parts of Artemisia messerschmidtiana - Suleimen, Ye.M.; Mamytbekova, G.K.; Serikbai, G.; Birimzhanova, D.A.; Doudkin, R.V.; Gorovoy, P.G.; Ross, S.; Martins, C.H.G. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2025)
The study of the chemical composition of biologically active compounds from plants of the natural flora is a promising direction for investigating their biological activity and potential use as sources for the medicinal, pharmaceutical, and cosmetic industries. This article presents the results of an evaluation of the composition and biological activity of essential oil isolated from Artemisia messerschmidtiana from the Far East. The es-sential oil was extracted by hydrodistillation. The obtained essential oil was tested for cytotoxic, fungicidal, antimicrobial, antimalarial, tuberculostatic, and antileishmanial activities. The composition of the extracted essential oil was analyzed by GC–MS methods. The total composition of the essential oil included 43 compo-nents, with the highest content observed for 1,8-cineole, camphor, and α-campholenal. Testing of the essen-tial oil revealed weak antimicrobial, fungicidal, and antimalarial activities, and high cytotoxic activity. No antituberculosis or antileishmanial activity was detected in the essential oil. The results contribute to the un-derstanding of the biological activity of components of the genus Artemisia L.
Keywords: Artemisia messerschmidtiana; essential oil; biological activity; chromatography-mass spectrome-try